PENGARUH EFEKTIVITAS LAYANAN DAN TRANSACTION SECURITY TERHADAP PENGGUNAAN APLIKASI DANA - Wijaya, Andini; Pandriadi, Pandriadi; Dini, Maya (Jurnal Akuntansi, Auditing dan Investasi, 2025)
The research aims to determine the influence of service effectiveness factors and transaction security factors on the use of the DANA application. The Likert scale is used to base quantitative research by determining respondents adopting the purposive sampling method. The research uses service effectiveness and transaction security as independent variables and use of the DANA application as a dependent variable. The testing method is multiple regression analysis. In partial results, it was found that the variables Service Effectiveness (X1) and Transaction Security (X2) had a positive and significant effect on the DANA Application Usage variable (Y).Keywords : E-wallet DANA, transaction security; service effectiveness; online transaction; cybercrime.